Unlocking nature’s pharmacy: an in-depth exploration of phytochemicals as potential sources of anti-cancer and anti-inflammatory molecules - Shifana C. Sadiq; Maria Pellissery Joy; Sreekumar U. Aiswarya; Abhishek Ajmani; Chenicheri K. Keerthana; Tennyson P. Rayginia; Noah Isakov; Ruby John Anto (Exploration of Drug Science)
Phytochemicals, the bioactive compounds derived from plants, play a significant role in modulating pathways leading to cancer and inflammation, rendering themselves promising candidates for therapeutic interventions. This review explores the multifaceted potential of various phytochemicals in modulating key mechanisms involved in the development and progression of cancer and inflammation. The diverse array of phytochemicals discussed here encompasses polyphenols, flavonoids, alkaloids, terpenoids, and many others, each with distinct molecular targets and modes of action. This review is an attempt to elucidate and correlate the regulatory role of phytochemicals on cellular signaling pathways implicated in oncogenesis and inflammatory responses, highlighting the significance and potential of phytochemical-based therapies for cancer prevention and treatment, as well as for managing inflammatory conditions. By exploring the promising potential of phytochemical-based remedies for cancer prevention, treatment, and inflammatory conditions and emphasizing their diverse roles in modulating critical regulatory mechanisms, this review addresses the current research landscape, challenges, and future directions in utilizing phytochemicals as effective agents against cancer and inflammation.